Роль нарушений обмена азотистых соединений в патогенезе рассеянного склероза = Role of metabolic disorders of nitrogen compounds in the pathogenesis of multiple sclerosis - O. Uy. Naumenko; A. I. Gozhenko (Journal of Education, Health and Sport, 2015)
Naumenko O. Uy., Gozhenko A. I. Роль нарушений обмена азотистых соединений в патогенезе рассеянного склероза = Role of metabolic disorders of nitrogen compounds in the pathogenesis of multiple sclerosis. Journal of Education, Health and Sport. 2015;5(10):262-268. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32879